Ethanolic extract of Descurainia sophia seeds sensitizes A549 human lung cancer cells to TRAIL cytotoxicity by upregulating death receptors. Issue 1 (December 2016) - Park, Jong-Shik; Lim, Chae; Bang, Ok-Sun; Kim, No
Abstract Background Our previous genome-wide gene expression analysis revealed that tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) death receptors 4 (DR4) and 5 (DR5) are markedly upregulated by the ethanolic extract ofD. sohia seeds (EEDS) in A549 TRAIL-refractory cancer cells. In the present study, we investigated whether the EEDS-mediated upregulation of TRAIL death receptors was associated with increased TRAIL-mediated toxicity in A549 cells in vitro. Methods Cell proliferation and viability were determined by an automatic cell counter. Gene silencing was performed by introducing small interfering RNA into cells. Expression changes of cellular proteins were determined by western blot analysis. Apoptotic cell death was monitored by western blot analysis. Analysis of variance followed by thepost-hoc Dunnett's test was used to compare the data. Results EEDS treatment increased both mRNA and protein levels of DR4 and DR5 in the TRAIL refractory A549 cells. Co-treatment of A549 cells with sub-lethal dose of EEDS and recombinant TRAIL increased the apoptotic cell death. Upregulation of DR5 by EEDS was mediated by an endoplasmic reticulum stress-induced transcription factor, CCAAT/enhancer-binding protein homologous protein (CHOP), and knockdown of CHOP expression inhibited EEDS-induced DR5 upregulation and abolished the EEDS-associated increase in TRAIL toxicity in A549 cells. Conclusions EEDS can sensitize A549 cells to TRAIL cytotoxicity by upregulation of TRAIL death receptors. Our findings suggested that EEDS is a good initial herbal source for the development of an anticancer supplement for anticancer therapeutics associated with TRAIL.